Factor Structure Specificity of Intercultural Competence Among International Relations Students: A Gender Perspective - Елена Н. Махмутова; Анфиса А. Чуганская; Елена В. Воевода (Rossijskij psihologičeskij žurnal., 2020)
Introduction. This study focuses on intercultural competence of students of international relations and aims to determine the characteristics of intercultural competence in the group of Russian male and female students of international relations. Methods. The ideas of the Council of Europe document on key competencies underlying the culture of democracy were the source material for the study of intercultural competence. We interviewed 54 students of international relations aged 17–23 years using the technique of M. Barrett who operationalized this conceptual model of the Council of Europe. This paper represents a first effort in comparing the factor structure of theoretical and empirical models of Russian respondents’ intercultural competence (taking into account their gender) in relation to their values, behavioral attitudes, practical skills, and knowledge necessary for intercultural interaction. Results. The study involving Russian respondents confirmed the hypothesis that there are no differences in the number of factors in the theoretical and empirical models of intercultural competence. In the group of Russian female students the rating of factors of intercultural competence was as follows: 1 – practical skills, 2 – tolerance, 3 – empathy, and 4 – civic consciousness. In the group of Russian male students the rating of factors of intercultural competence was as follows: 1 – respect and responsibility, 2 – adaptability, 3 – empathy, and 4 – tolerance. Discussion. The findings obtained from the Russian sample suggest that while maintaining the four-factor structure in the theoretical and empirical models of intercultural competence, the content of factors differs significantly from the theoretical model. In our research, the respondents showed semantic and instrumental diversity in the components of intercultural competence. Women associate the success of intercultural interaction with skills, self-education, skills for listening and understanding, willingness to cooperate, and tolerance. For men, the success of intercultural interaction depends on respect and responsibility, adaptability, knowledge and its critical understanding. The conceptual model for the development of intercultural competence should be improved taking into account gender and professional characteristics of students and should be implemented in educational programs.